A retrospective histopathological, immunohistochemical and molecular study of the presence of Leishmania spp. in the skin of cats with head and neck ulcerative dermatitis. Issue 3 (25th March 2018) - Di Mattia, Diana; Fondevila, Dolores; Abramo, Francesca; Fondati, Alessandra
Abstract : Background: Head and neck ulcers in cats can arise from allergic and nonallergic disorders, including feline leishmaniosis (FeL). It is important to rule out this aetiological agent in regions that are endemic for canine leishmaniosis, because the drugs used to treat immune‐mediated disorders of cats can be contraindicated in the setting of infection. Hypothesis/Objectives: The aim of this study was to evaluate the skin of cats with ulcerative dermatitis of the head or neck for evidence of Leishmania infection using combined immunohistochemistry (IHC) and Polymerase Chain Reaction (PCR). An IHC for tissue histiocytes was also utilized because leishmaniosis may provoke a histiocytic inflammatory response. Animals: Twenty seven cats with head and/or neck ulcers. Methods: Skin biopsy specimens were examined for the presence of Leishmania spp. by routine histopathological evaluation and IHC using a polyclonal anti‐ Leishmania antibody, and by quantitative PCR (qPCR). The ionized calcium‐binding adapter molecule‐1 (IBA‐1) antibody was used to immunolocalize histiocytes. Selected history and clinical data were recorded. Results: All specimens showed a superficial mid‐perivascular mixed inflammatory infiltrate. The presence of histiocytes was confirmed in 23 of 27 cases with the IBA‐1 antibody. Immunohistochemistry and qPCR techniques confirmed the absence of Leishmania in all cases. Conclusions and clinical importance: Leishmania did not seem to play a role in the pathogenesis of feline ulcerative dermatitis of the head and neck in the subjects studied, despite a lifestyle potentially associated with infection. Histiocytic infiltration of tissue is not a specific marker for Leishmania infection in this population. Abstract : Background – Cutaneous head and neck ulceration in cats can arise from allergic and nonallergic disorders, including feline leishmaniosis (FeL). It is important to rule out this aetiological agent in regions that are endemic for canine leishmaniosis, because the drugs used to treat immune‐mediated disorders of cats can be contraindicated in the setting of infection.Hypothesis/Objectives – The aim of this study was to evaluate the skin of cats with ulcerative dermatitis of the head or neck for evidence of Leishmania infection using combined immunohistochemistry (IHC) and PCR. An IHC for tissue histiocytes also was utilized because leishmaniosis may provoke a histiocytic inflammatory response.Conclusions and clinical importance – Leishmania did not seem to play a role in the pathogenesis of feline ulcerative dermatitis of the head and neck in the subjects studied, despite a lifestyle potentially associated with infection. Histiocytic infiltration of tissue is not a specific marker for Leishmania infection in this population.